Analisis Kinerja Ekonomi, Sosial, dan Lingkungan Social Entrepreneurship Warung Sehat 1000 Kebun - Riyanti, Fauziah; Charina, Anne (Universitas Galuh, 2025)
This research aims to analyze economic, social performance and environmental applications as well as socialpreneurship elements in a business. This research was conducted using a qualitative design with a case study approach at Warung Sehat 1000 Kebun Bandung City, the determination of informants was carried out purposively. Data analysis uses disclosure of each item of performance indicators according to the Global Reporting Initiative (GRI). The results of the research show that the operations of Warung Sehat 1000 Kebun apply the four elements of sociopreneurship, the GRI indicator items which reveal economic performance show that Warung Sehat 1000 Kebun as a sociopreneurship can still gain profits for its business operations to carry out its social activities, in terms of the social performance of Warung Sehat 1000 Kebun creating and absorbing local workers, helping local organic farmers who have difficulty accessing organic markets, and involving local communities in various social activities, and in terms of environmental performance Warung Sehat 1000 Kebun contributes to minimizing the problems caused by the burning of the Sarimukti City Final Disposal Site Bandung as a form of responsibility and active participation in environmental conservation.